2021
DOI: 10.1038/s41598-021-82743-x
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life of children with neurodevelopmental disorders and their parents during the Coronavirus disease 19 emergency in Japan

Abstract: This study aimed to reveal how the COVID-19 stay-at-home period has affected the quality of life (QOL) of children with neurodevelopmental disorders and their parents and to identify possible factors that enabled them to maintain their QOL. We enrolled 136 school-aged children (intellectual quotient ≥ 50) and their parents and administered QOL questionnaires to assess the maladaptive behavior of the children; depression, anxiety, and stress of the parents; and activities of their daily lives. The relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 34 publications
(49 reference statements)
2
39
2
1
Order By: Relevance
“…In fact, the majority of children with autism spectrum disorder (ASD) had a higher probability of worsened behavioral symptoms during the pandemic than during the pre-COVID-19 era, and the need for professional support as perceived by parents was more for children with NDDs than for TDC 2 , 5 . Moreover, in a previous study, the prevalence of maternal depression increased especially in children with NDDs during the COVID-19 pandemic 6 , 7 , and maternal depressive state negatively interacted with changes in lifestyles and maladaptive behaviors of children with NDDs during the COVID-19 pandemic 1 , 3 5 , 8 . This negative interaction was observed between children with NDDs and their caregivers during ordinary times 9 , 10 and previous natural disasters prior to the COVID-19 pandemic 11 , and was even worse during emergency situations.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In fact, the majority of children with autism spectrum disorder (ASD) had a higher probability of worsened behavioral symptoms during the pandemic than during the pre-COVID-19 era, and the need for professional support as perceived by parents was more for children with NDDs than for TDC 2 , 5 . Moreover, in a previous study, the prevalence of maternal depression increased especially in children with NDDs during the COVID-19 pandemic 6 , 7 , and maternal depressive state negatively interacted with changes in lifestyles and maladaptive behaviors of children with NDDs during the COVID-19 pandemic 1 , 3 5 , 8 . This negative interaction was observed between children with NDDs and their caregivers during ordinary times 9 , 10 and previous natural disasters prior to the COVID-19 pandemic 11 , and was even worse during emergency situations.…”
Section: Introductionmentioning
confidence: 78%
“…In this study, we evaluated the quality of life (QOL) of children with NDDs and their parents in the early period of COVID-19 pandemic (May 2020; T1) and one year later (May 2021; T2) during the pandemic. The QOL describes an individual’s subjective perception of their position in life, as evidenced by their physical, psychological, and social functioning, and is often used to examine well-being and burden in children with NDDs and parents 8 , 13 . During the early period of the COVID-19 pandemic, previous studies revealed that higher QOL of children with NDDs and their parents was associated with less parental stress, parental depression and anxiety, and milder maladaptive behavior in children 8 .…”
Section: Introductionmentioning
confidence: 99%
“…A Turkish study during the COVID-19 pandemic indicated that severe sleep disorders led to highly increased ASD symptoms ( 32 ). In our previous study, QOL of children in parent proxy-reports also decreased with changes in sleep during the COVID-19 stay-at-home period ( 19 ). Despite a weak correlation of the same domain in both reports in a previous study ( 20 ), the similarity of the results in self-report and proxy-report was clarified in this study.…”
Section: Discussionmentioning
confidence: 82%
“…In a previous study, we asked parents to respond to the questionnaire survey on changes in children's QOL and lifestyle during the COVID-19 stay-at-home period. We found that changes in children's sleep schedules were associated with reduced QOL, and decreased maladaptive behavior with a maintained QOL ( 19 ). Thus, our former study indicated the importance of adjusting the sleep schedule to maintain the QOL of children.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in children and adolescents with diseases such as attention deficit hyperactivity disorder (ADHD) and autism, fluctuations and increases in their symptoms emerged in this process. This statement also negatively affected the mood of the parents and caregivers [91][92][93]. Sleep disturbances in children and adolescents with ADHD were also reported [94].…”
Section: Mental Problems Due To Chronic Stress and Social Isolationmentioning
confidence: 96%